Gambaran Kualitas Hidup Penderita Tuberkulosis Resistan Obat dan Karakteristiknya di Kabupaten Banyumas, Provinsi Jawa Tengah, Periode Tahun - Imam Abrori; Riris Andono Ahmad (Berita Kedokteran Masyarakat (BKM), 2018)
Quality of life among patients with multi-drug resistant tuberculosis in the district of BanyumasPurposeThis study was conducted to investigate the quality of life among patients with multi-drug resistant tuberculosis and to examine factors associated with them. MethodsData from an in-depth interview, involved 22 patients with multi-drug resistant tuberculosis, were used in this study. ResultsThis study showed 54.5% males, 50.0% adults, 59.1% married, 22.7% divorced, 72.7% lived in rural, 95.5% had basic education, 45.5% as a private employment (before sick), 77.3% as unemployment (after sick), 72.7% low income, 54.5% in continuation phase, 95.5%  re-treatment (45% relapse and 40.9% failure cases), 90.9% had drugs side effects (mild/severe); 36.4% had comorbidity; 45.5% smokers, 31.8% falcoholics; 54.5% lack of social support; 31.8% poor and 36.4% moderate quality of life. ConclusionPatients with multi-drug resistant tuberculosis had a worse quality of life and lack social support. Health worker needs to improve their quality of life and social support through establishing a peer support groups to give counseling, information education, communication, motivation, and skills training for them.